An Integrated Green Supply Chain Model For Indonesian MSMEs: Internal-External Drivers, Practices, and Performance - Ernawati, Erni; Fauziana, Diyah Ratna; Yunus, Erlinda Nusron (Business Review and Case Studies, 2025)
Background: The development of a green economy as one of the pillars in driving the national economic growth target of 6%-7% towards the Vision of Golden Indonesia 2045 continues to be encouraged. Several national green indicators still need to be improved, especially related to industrial sector activities. In Indonesia, most industrial actors (99%) are MSMEs, contributing 61% of GDP. Improving MSME green behavior and supply chain performance is crucial for enhancing Indonesia’s green economy. Purpose: The purpose of this study was to build an integrated green supply chain model in the MSME ecosystem to support the development of a green economy. Design/methodology/approach: This study used a quantitative approach and CB-SEM analysis tools. The study processed questionnaire data from 459 MSME respondents collected during the period August - October 2024. Findings/Result: The study produced an integrated green supply chain model in the MSME ecosystem in Indonesia, which shows that external forces have a greater influence on green management practices than internal forces. Green management practices then have a significant influence on green economic performance, green social performance, and green environmental performance. Conclusion: Green management practices have the greatest influence on green environmental performance. The results of this study provide implications that managers should prioritize external collaborations, regulations, and stakeholder engagement to enhance green practices. Emphasizing green management will improve environmental performance, realization of green economy and aligning with 2045 Indonesia’s Vision. Originality/value (State of the art): Improving MSME green behavior and supply chain performance is crucial for enhancing Indonesia’s green economy, yet research remains limited.Keywords: green management practices, green performance, integrated green supply chain, internal-external drivers, MSMEs